Pendekatan Catching-Up Product Cycle Untuk Industri Elektronika Di Indonesia - Masykur Wiratmo (Universitas Islam Indonesia, 2002)
Catching-up product cycle (CPC) is still as powerful framework to analyze industrial performance, especially for foot-loose industry such as electronics in Indonesia although the CPC approach is established in Japan having different culture, social-politics and economic environment. The CPC can explain well the development of industry.Indonesian electronic industry has grown since Indonesia industrialized its economy. However, almost 20 years electronic Industry grew slowly as the CPC framework reflects it. Based on industrial life cycle, Indonesian electronic industry is at the second stage that is import substitution, during 1993-1996. Relatively unskilled human resources may cause it.